Early growth response‐1‐mediated down‐regulation of drebrin correlates with loss of dendritic spines. Issue 1 (26th April 2017) - Cho, Chulmin; MacDonald, Ryen; Shang, Jijun; Cho, Moon Jeong; Chalifour, Lorraine E.; Paudel, Hemant K.
Abstract: Post‐synaptic dendritic spines are structurally composed of actin cytoskeleton, which undergoes dynamic morphological changes to accommodate incoming synaptic activity. Drebrin is an actin‐binding protein highly expressed in dendritic spines that serves an important role in regulating spine morphology. Functionally, loss of drebrin directly correlates with deficits in learning and memory, as is the case observed in Alzheimer's disease. Despite these findings, the regulatory factor responsible for drebrin loss remains unclear. Here, we show that early growth response‐1 (Egr‐1), an inducible zinc finger transcription factor, down‐regulates drebrin expression. Chromatin immunoprecipitation analyses identified Egr‐1 binding sites upstream of the drebrin start site in neuronal cells. Over‐expression of Egr‐1 in vitro in primary hippocampal neurons or in vivo in homogenates prepared from the hippocampi of an inducible mouse model of Egr‐1 show reduced drebrin mRNA and protein levels. Conversely, increased drebrin was detected in hippocampal samples isolated from Egr‐1‐deficient brain. These data demonstrate that Egr‐1 interacts with the drebrin promoter and negatively regulates drebrin expression. Furthermore, immunocytochemical and Golgi staining analyses revealed reduced drebrin protein and dendritic spine density as well as reduced expression of synaptic markers in in vitro hippocampal neurons over‐expressing Egr‐1 and in vivo inducible mouse model of Egr‐1. In contrast, increased drebrin expression correlated with increased dendritic spine density was detected in samples from Egr‐1‐deficient mice. These data provide evidence that Egr‐1 is a novel regulator of drebrin expression, which is linked to changes in dendritic spine density. Abstract : Drebrin is an actin‐binding protein present in dendritic spines and is essential in formation and maintenance of dendritic spine morphology. Here, we propose that early growth response‐1 (Egr‐1) transcription factor negatively regulates drebrin expression. Specifically, Egr‐1 up‐regulation leads to down‐regulation of drebrin mRNA and protein and results in a decrease in dendritic spine density. Conversely, we demonstrate that Egr‐1‐loss‐of‐function leads to increased drebrin expression and results in an increase in dendritic spine density.